Status Gizi dengan Kejadian Anemia Pada Ibu Hamil - Risma Putri Utama (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: one of the problems of poor nutrition for pregnant women is anemia, where there is a decrease in the quantity and quality of red blood cells, this is exacerbated by the hemodilution process in pregnancy so that hemoglobin levels decrease which has the potential to increase the risk of maternal and fetal morbidity and mortality. Aim; determine the relationship between the nutritional status of pregnant women with the incidence of anemia. Methods: analytic research with cross-sectional approach, the number of samples is 78 people with non-random sampling technique. Manual data processing with Chi-Square statistical test. Result: that there is no relationship between nutritional status and the incidence of anemia in pregnant women with a value of X² (count) = 13,503. Conclusion: that there is a relationship between nutritional status and the incidence of anemia in pregnant women. Giving iron tablet supplementation to pregnant women is recommended in one day two tablets (one tablet contains 60 mg Fe and 200 ug folic acid)